Walking and taking vitamin C alleviates oxidative stress and inflammation in overweight students, even in the short-term - Zhang, Qian; Guo, Miao; Chen, Tianyi; Cheng, Huizhi; Yang, Qianwen; Zhao, Zhuohui; She, Rong; Yang, Xiaoyan; Xiao, Wen; Yang, Xu; Li, Lijuan (Frontiers in Public Health, 2022)
Objective: Being obese or overweight are risk factors for major chronic diseases, and oxidative stress and inflammation may be one of the molecular mechanisms leading to the persistence of these chronic diseases. Discovering interventions to alleviate oxidative stress and inflammation in the overweight/obese population, is very important for public health and health education. Methods: A two-week panel intervention study (Run0-Run1-Run2) was conducted. The subjects were 77 overweight/obese undergraduates attending Dali University, with a BMI>24kg/m2. The physical indices measured at the end of each run included BMI, waist circumference, serum ROS, TNF-α, IL-1β and urinary 8-OHdG. Students were allocated to one of four intervention groups: 0 treatment (control); walking; taking vitamin C; and walking + taking vitamin C. Results: The results demonstrated (1) Walking significantly alleviated ROS levels, and this was consistent in Run1 and Run2; (2) During Run1, all three intervention modes reduced levels of 8-OHdG, but there was a statistically insignificant increase during Run2; (3) No alleviating effects of the three intervention modes on TNF-α levels during Run1 and Run2 were observed; (4) The alleviating effects of the three intervention modes on IL-1β levels during Run1 and Run2 were clear. Conclusion: Walking and taking vitamin C can reduce levels of ROS, 8-OHdG and IL-1β, but not TNF-α, in overweight/obese participants. These interventions may become potential preventive measures for the overweight against obese-induced oxidative stress and inflammation.